Anti-inflammatory activity and phytochemistry of the leaf extracts of Baccaurea sylvestris Lour - Ho Van Ban; , Vu Van Chien; Nguyen Thi Hue; Pham Thi Hang; Pham Van Cuong; Nguyen Quoc Vuong; Nguyen Le Tuan (Vietnam Journal of Science and Technology, 2024)
Baccaurea is a genus of plants in the family Phyllanthaceae. Many species of the Baccaurea had available bioactivities. They have been used in many countries from Indo-Malaysia to the Western Pacific. However, chemical components of this genus haven’t been studied in detail. Among these species, Baccaurea sylvestris Lour have never studied in the world and Viet Nam. From the leaf extracts of B. sylvestris Lour collected Kbang district, Gia Lai province, Viet Nam, anti-inflammatory activity and phytochemistry were reported. The n-hexane (BSH) and ethyl acetate (BSE) extracts from leaves inhibited NO production in lipopolysaccharide-induced RAW 264.7 cells with IC50 values of respectively, without cell toxicity. In addition, from these extracts seven known compounds including friedelin (1), 3β-friedelanol (2), stigmast-4-en-3-one (3), (-)-epiafzelechin (4), 4-hydroxybenzaldehyde (5), 4-hydroxybenzoic acid (6), and 3,4,5-trimethoxyphenyl-O-β-D-glucopyranoside (7) were isolated. Their chemical structures were determined by ESI-MS and 1D and 2D NMR spectral analyses and compared with the literature data. These compounds were firstly isolated from B. sylvestris Lour. These compounds had available anti-inflammatory activity as previous reports.